Mathematical Model for Water Desalination of the Third River-Northern Section - عز الدين علي, أنغام; حسن مسلم, زينب (Journal of Engineering and Sustainable Development, 2006)
This research includes developing a computer program to improve the water quality of the third river-northern section by maintaining the EC and SAR values within the allowable limits for irrigation. This has been suggested to be done by the construction of desalination plants on the drainages along the river, operating with a minimum cost to achieve the desired pollutant limit. The influence of drainage changes and the maximum limit of pollutants at cost is also considered in this program.